2020
DOI: 10.1080/13548506.2020.1842473
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychological distress among the public in Oman amid coronavirus disease 2019 pandemic: a cross-sectional analytical study

Abstract: Coronavirus disease 2019 (COVID-19) is a global, virulent pandemic disease that emerged in December 2019, with both short-and longterm psychological repercussions being inevitable. This study aimed to investigate the prevalence and predictors of psychological distress, defined by the presence of either depression or anxiety, among the public in Oman during the COVID-19 pandemic. This was a web-based, cross-sectional study conducted using governmental and private institutional e-mail systems and social media pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…As noted, only a select few demographics, COVID-specific demands, and external resources variables emerged as significant predictors when accounting for the strong contribution of psychological resources. This is in contrast to prior COVID-19 studies that have identified age (e.g., Elbay et al, 2020), gender (e.g., González-Sanguino et al, 2020), SES (e.g., Sinawi et al, 2021), and social support (e.g., Liu, Zhang, et al, 2020) as predictors of distress or adaptation. This discrepancy is likely due to prior studies' reliance on regression or group comparison models that do not account for the examination of a large number of variables simultaneously.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…As noted, only a select few demographics, COVID-specific demands, and external resources variables emerged as significant predictors when accounting for the strong contribution of psychological resources. This is in contrast to prior COVID-19 studies that have identified age (e.g., Elbay et al, 2020), gender (e.g., González-Sanguino et al, 2020), SES (e.g., Sinawi et al, 2021), and social support (e.g., Liu, Zhang, et al, 2020) as predictors of distress or adaptation. This discrepancy is likely due to prior studies' reliance on regression or group comparison models that do not account for the examination of a large number of variables simultaneously.…”
Section: Discussioncontrasting
confidence: 89%
“…Researchers attempting to identify predictors of mental health outcomes related to COVID‐19 have primarily applied traditional statistical methods that examine group differences or relationships between discrete variables. These studies have identified female gender (González‐Sanguino et al, 2020 ; Mazza et al, 2020 ; Özdin & Bayrak Özdin, 2020 ; Wang et al, 2020 ), younger age (Elbay et al, 2020 ; González‐Sanguino et al, 2020 ; Huang & Zhao, 2020 ), pre‐existing mental health conditions (Asmundson et al, 2020 ; González‐Sanguino et al, 2020 ; French et al, 2020 ; Özdin & Bayrak Özdin, 2020 ; Usher et al, 2020 ), poorer physical health (Zhou et al, 2020 ; Wang et al, 2020 ), financial instability (Sinawi et al, 2021 ), financial loss due to COVID‐19 (Hyland et al, 2020), and social isolation or loneliness (Asmundson et al, 2020 ; Brooks et al, 2020 ; González‐Sanguino et al, 2020 ; Liu, Zhang, et al, 2020 ) as risk factors for COVID‐related distress. Research on the influence of psychological resources has identified an array of psychosocial risk factors of psychological distress during the pandemic, including high fear and exaggerated beliefs about the dangerousness of COVID (Taylor et al, 2020 ; Zacher & Rudolph, 2020 ), maladaptive coping strategies including denial, self‐blame, and substance use (Rettie & Daniels, 2020 ), intolerance of uncertainty (Glowacz & Schmits, 2020 ; Rettie & Daniels, 2020 ), low openness to experience (Kroska et al, 2020 ), avoidant coping (Dawson & Golijani‐Moghaddam, 2020 ; Mariani et al, 2020 ), hopelessness (Shanahan et al, 2020 ), and high levels of rumination (Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certain demographic groups were identified as having a higher prevalence of anxiety or being more at risk of developing adverse mental health issues. Twenty-two studies found that females consistently had higher levels of anxiety than males [ 11 , 28 , 31 , 32 , 33 , 35 , 39 , 41 , 62 , 63 , 65 , 75 , 79 , 82 , 86 , 88 , 92 , 94 , 96 , 102 , 105 , 110 ]. However, two studies found that males were more anxious when living with dependents under 18 [ 50 , 61 ] and that younger males had higher instances of anxiety [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Second, the study included only female clients, and the research conducted during the COVID-19 pandemic among the public in Oman has shown that the female gender is an independent risk factor to developing psychological stress. 42 Moreover, Omani women have a more positive attitude toward mental illness compared to Omani men. 43 Therefore, Omani women are more likely to seek mental health services.…”
Section: Discussionmentioning
confidence: 99%